West African agriculture and climate change: A comprehensive analysis - Nigeria - Hassan, Shuaib M.; Kuenobe, Celestine E.; Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
About half of the working population in Nigeria is engaged in agriculture. Cassava is the most important food crop. Other major food crops include yam, sorghum, and maize. The share that agriculture contributes to GDP has declined from about 50 percent in 2000 to about 30 percent.